Ethnographic methods in libraries revisited - Philip Hider; Simon Wakeling; Jane Garner (Information Research: An International Electronic Journal)
Introduction. Ethnography has increasingly been utilised by social science researchers outside of social and cultural anthropology. We report here an analysis of the extent and nature of its use in library studies research over the past decade.